PEMBIASAAN PERILAKU ISLAMI PESERTA DIDIK MELALUI PROGRAM KEAGAMAAN DI SEKOLAH (PENELITIAN DI SMPN 1 KOTA GARUT) - Aja Rowikarim (HASBUNA : Jurnal Pendidikan Islam, 2022)
The condition of some teenagers today tends to be anarchist, criminal, bullying, fights, sex before marriage, forgetting manners, missing adab, arrogant students have become a daily sight. This certainly causes problems, because these behaviors are not in accordance with the ideals of the Indonesian nation that, formal school institutions established actually realize a generation of noble character. The purpose of this study is to analyze: programm process, imlikasi Islamic behavior of learners through religious programs in schools. This research is qualitative research with descriptive analytical methods. Data collection techniques are carried out through interviews, observations, and literature.The research subjects are the principal, student waka, curriculum waka, some teachers and some students. Data analysis is done by having data obtained then collected for analysis and conclusions. From this study, it was concluded that by instilling the habituation of Islamic behavior through religious programs in schools, it can form students who have the supreme or religious godhead, love to worship and behave well.